2023
DOI: 10.3390/jcm12020639
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative CT Metrics for the Prediction of Therapeutic Effect in Asthma

Abstract: Background: Few studies have explored the correlation between asthma medication and features on HRCT images. We aim to analyse the differences and temporal changes of lung function and airway resistance in asthma with diverse HRCT phenotypes in a short period after inhalation of budesonide/formoterol. Method: This observational study recruited 55 adult patients with varying severities of asthma. We performed detailed airway metrics measurements of chest CT scans, such as airway wall thickness (WT), wall area p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…HRCT scans of the chest can display the ratio of bronchial wall thickness to bronchial diameter, which is associated with subepithelial brosis in bronchial pathology [28]. Previous research has found that asthma patients exhibit an increased ratio of bronchial wall thickness to outer diameter compared to normal individuals, allowing a more visual and intuitive display of airway remodeling levels [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HRCT scans of the chest can display the ratio of bronchial wall thickness to bronchial diameter, which is associated with subepithelial brosis in bronchial pathology [28]. Previous research has found that asthma patients exhibit an increased ratio of bronchial wall thickness to outer diameter compared to normal individuals, allowing a more visual and intuitive display of airway remodeling levels [11].…”
Section: Discussionmentioning
confidence: 99%
“…This study utilized imaging software, 3D Slicer [11], to reconstruct the bronchial wall structure and automatically measure bronchial wall parameters. A comparative analysis was performed to investigate the changes in bronchial wall thickness, bronchial lumen area, and other related parameters in asthma patients before and after treatment with omalizumab.…”
Section: Introductionmentioning
confidence: 99%